Gambaran Pengetahuan Perawat Tentang Perawatan Orang Dengan HIV/AIDS (ODHA) Sebelum Dan Sesudah Pendidikan Kesehatan - Aziza, Mira "; ", Safri "; Elita, Veny " (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Keperawatan, 2017)
AbstractHuman Immunodeficiency Virus (HIV) is a virus that attacks white blood cells in the body (lymphocytes) which resulted in the decline of the human immune. While the Acquired Immuno Deficiency Syndrome (AIDS) is a syndrome or collection of symptoms in a disease caused by a retrovirus that attacks the immune system or the body's defense. This study aims to describe the nurse's knowledge on the care of people living with HIV / AIDS (PLWHA) before and after health education with a simple descriptive research design. The research samples were 15 nurses who were taken based on inclusion criteria. Measuring instrument used was a questionnaire about nurse knowledge to care of people living with HIV / AIDS (PLWHA). The analysis used univariate analysis to determine the frequency distribution and knowledge of nurses overview of PLHA before and after health education. Results of univariate analysis study showed that most of the respondents aged 26-35 years (60%), female gender (73.3%), education level DIII (86.7%), work 6-10 years old (46.7%) , who did not attend training AIDS (73.3%). Average knowledge of health education nurse before being given was 52.92; the minimum value was 37.50 and the maximum one was 81.25 . Otherwise there was an increased knowledge as much as 38.74 points with an average value of 91.66, the minimum value was 81 and the maximum one was 100 after being given health education. The results of analysis study illustrate an increase in the average value of a given health education before and after being given health education. Suggested to the leadership of health centers to provide training on HIV / AIDS. Keywords: Health Education, HIV / AIDS, Knowledge, ODHA